Victim Narratives and Cancel Culture: A Victimological Analysis in the Era of Digital Social Justice - Konoras, Isyana Kurniasari; Muhammad, Zakiyyu (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
Abstract The proliferation of cancel culture in the digital era has introduced new complexities in the social construction of victimhood and perpetration. These labels are often assigned rapidly, shaped more by public perception on social media than by formal legal mechanisms. This study employs a critical victimology lens to examine how victim and perpetrator narratives are constructed, circulated, and contested in digital spaces. Using qualitative discourse analysis of selected viral cases in Indonesia, the findings reveal that the identities of victims and perpetrators are fluid and contingent upon prevailing public narratives. These insights underscore the need for a justice system that is adaptive and reflective of evolving social dynamics in digital contexts. Keywords: critical victimology, cancel culture, social media, victim-perpetrator narratives, digital justice